Strategi Komunikasi Pemasaran Tarif Dinamis PT. Kai (Persero) DAOP VII Madiun: Studi Kasus Di Stasiun Blitar - Veiling Bunga Adista; Anita Reta Kusumawijayanti; Hanik Amaria (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the marketing communication strategy of the dynamic fare system implemented by PT. KAI (Persero) DAOP VII Madiun, with a case study at Blitar Station. The dynamic fare system is a pricing mechanism in which ticket prices vary according to booking time and demand levels, thus requiring effective marketing communication to enhance passenger understanding and acceptance. This research employs a qualitative approach with data collected through interviews, observation, and documentation. The findings reveal that PT. KAI’s marketing communication strategy integrates five main instruments: digital advertising through social media and the KAI Access application, sales promotion in the form of discounts and bundling, public relations activities aimed at passenger education, digital marketing via YouTube and TikTok, and personal selling through direct communication between staff and passengers. Supporting factors include the utilization of digital technology, staff competence, and attractive promotions, while inhibiting factors consist of low digital literacy among elderly passengers, limited visual facilities at stations, and insufficient offline educational materials. This study recommends improving digital education facilities at stations, conducting staff training, and developing more creative and inclusive digital marketing content. The findings are expected to serve as a reference for PT. KAI (Persero) DAOP VII Madiun in optimizing its dynamic fare marketing communication strategy to enhance customer satisfaction and loyalty.